Pollination Mechanisms in Genus Terminalia Linn - Srivastava, P. K. (Indian Forester, 1993)
Studies on the pollination mechanisms of four species of genus Terminalia Linn. Conducted at Central Tasar Research& Training Institute, Ranchi revealed that pollination is entormophillous. Out of 22 insect pollinators collected a maximum number belonged to Lepidoptera (6), Diptera (6) and Hymenoptera (6) and bees play very important role in pollination.